Pengaruh Kemudahan Penggunaan dan Manfaat Terhadap Keputusan Penggunaan Quick Response Code Indonesian Standard (QRIS) pada Aplikasi DANA di Kota Mataram - Ardiansyah, M. Risky; Athar, Handry Sudhiarta (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
The purpose of this study is to determine the effect of the Ease of Use and Benefit variables on the Decision to Use QRIS in the DANA application in Mataram City. In this study, 100 respondents located in Mataram City were used as samples. Based on the data analysis, it can be concluded that the Ease of Use and Benefit variables have a positive and significant effect on the Decision to Use QRIS in the DANA application in Mataram City. The Ease of Use variable has a positive and significant effect on the Decision to Use QRIS in the DANA application in Mataram City, as evidenced by the rejection of H0 and the acceptance of H1. The Benefit variable has an effect on the Decision to Use QRIS in the DANA application in Mataram City, as evidenced by the rejection of H0 and the acceptance of H2.